Evidence - Choo, Andrew L.-T (Oxford University Press, 2006)
This new and exciting textbook provides a clear account of the key principles of the law of civil and criminal evidence in England and Wales, presented in a clear, accessible and readable manner. Although the book takes the relevant legal principles as the basis for discussion, it sets these principles against the background of a consideration of more fundamental issues such as the rationales underlying the law of evidence. The book achieves a successful mix of critical and thought-provoking analysis